2011
DOI: 10.1093/cercor/bhr152
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Functional Cortical ROIs via DTI-Derived Fiber Shape Models

Abstract: Studying structural and functional connectivities of human cerebral cortex has drawn significant interest and effort recently. A fundamental and challenging problem arises when attempting to measure the structural and/or functional connectivities of specific cortical networks: how to identify and localize the best possible regions of interests (ROIs) on the cortex? In our view, the major challenges come from uncertainties in ROI boundary definition, the remarkable structural and functional variability across i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 29 publications
6
73
0
Order By: Relevance
“…Recently we created and validated 358 cortical landmarks that have intrinsically established structural and functional correspondences in different brains [5], providing natural and ideal nodes for brain network construction. In brief, each of the 358 cortical landmarks was optimized to possess group-wise consistent white matter fiber connection patterns, which have been demonstrated to be predictive of functional localizations in the brain [5,7]. The neuroscience basis is that each brain's cytoarchitectonic region has a unique set of intrinsic axonal inputs and outputs, called the "connectional fingerprint" [8], which largely determines the functions that brain area can perform.…”
Section: Multimodal Brain Network Constructionmentioning
confidence: 99%
“…Recently we created and validated 358 cortical landmarks that have intrinsically established structural and functional correspondences in different brains [5], providing natural and ideal nodes for brain network construction. In brief, each of the 358 cortical landmarks was optimized to possess group-wise consistent white matter fiber connection patterns, which have been demonstrated to be predictive of functional localizations in the brain [5,7]. The neuroscience basis is that each brain's cytoarchitectonic region has a unique set of intrinsic axonal inputs and outputs, called the "connectional fingerprint" [8], which largely determines the functions that brain area can perform.…”
Section: Multimodal Brain Network Constructionmentioning
confidence: 99%
“…The intrinsic neuroscience foundation of the approach is that each brain's cytoarchitectonic area possess a unique set of extrinsic in and out, entitled the ''connectional fingerprint'' in (Passingham et al 2002), which principally determines the functions of each brain area. A variety of recent studies (Laird et al 2009;Passingham et al 2002;Zhu et al 2013;Zhang et al 2012) have confirmed and replicated this close relationship between structural connection pattern and brain function. In addition, this set of 358 structural brain landmarks can be accurately and reliably predicted in an individual subject based only on DTI data , demonstrating the remarkable reproducibility and predictability.…”
Section: Brain Response Modelingmentioning
confidence: 77%
“…In the literature, increasing number of studies have reported the dramatic dynamics of brain functions and interactions (Chang and Glover, 2010; Gao and Lin, 2012; Li et al, 2012b; Majeed et al, 2011; Smith et al, 2012; Spreng et al, 2010; Zhang et al, 2012a), that is, the brain undergoes remarkable functional dynamics in either resting state (Chang and Glover, 2010; Li et al, 2012b; Smith et al, 2012) or during task performances (Li et al, 2012b; Zhang et al, 2012a). Thus, the lack of those dynamics can substantially influence the reliability and robustness of the learned encoding/decoding models based on the fundamental assumption of temporal stationarity.…”
Section: Other Challengesmentioning
confidence: 99%